Article RETRACTED due to manipulation by the authors The effect of a holistic approach training model on increasing the speed and agility of tennis athletes - Alnedral Alnedral; Rices Jatra; Kamal Firdaus; Hendri Neldi; Syahrial Bakhtiar; Damrah Damrah; Masrun Masrun; Nissa Aldani; Yendrizal Yendrizal; Yovhandra Ockta; Rifqi Festiawan (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Purpose: Physical condition is an essential element required by tennis athletes. Without proper physical conditioning, players cannot perform optimally. The physical condition of tennis athletes at Club Nusalima, Pekanbaru, Indonesia, is still not optimal, as evidenced by their low achievements this year, with no athletes ranked nationally by Pelti. Two of the most important physical conditions required by tennis players are agility and speed. Methods: This study aimed to determine the effect of a training method using a holistic approach on improving the physical condition—specifically agility and speed—of tennis athletes at Club Nusalima, Pekanbaru, Indonesia. The research was conducted as an experimental study using purposive sampling, with a sample consisting of 10 young athletes aged 15-17 from the club. The research design used was a "One Group Pretest-Posttest" approach. The instruments used to collect data were the 505 Agility Test and the 20-meter sprint test for speed. Results: The data analysis technique used was the t-test with a significance level of 5%. For agility, the results showed that the t-table value was 2.26 and the t-count value was 3.26, which is greater than 2.26, indicating a significant improvement in agility. Similarly, for speed, the t-test analysis showed that the t-count value was 3.04, which was also greater than the t-table value of 2.26, confirming a significant improvement in speed. Although the improvement in agility (0.24 seconds) was greater than the improvement in speed (0.07 seconds), both metrics showed a significant positive effect from the holistic training approach. Conclusion: The holistic training method significantly improved both agility and speed in tennis athletes at Club Nusalima. Agility improved from an average of 2.81 seconds to 2.74 seconds, and speed also showed measurable improvement from 3.04 seconds to 2.96 seconds. These findings suggest that the holistic approach is an effective model for enhancing physical performance in tennis players.